THE NEW CHALLENGES OF TOURISM AIRPORTS - THE CASE OF FARO AIRPORT - CLÁUDIA RIBEIRO DE ALMEIDA (Tourism & Management Studies)
Airport infrastructures play an important role in the heart of the regions in which they are located, as well as in certain sectors of activity, such as tourism. In recent years, their positioning has been altered from a passive attitude to an active attitude due to new market demands and new trends which have arisen in associated sectors, such as the air transport sector. The 1997 deregulation of air transport in Europe led to major changes on the way people travel. One of the most interesting results of deregulation, was caused by the fact that the low cost airlines appeared on the market with a business model distinct from the traditional scheduled and charter airlines, allowing for the opening up of new airports and new tourist destinations. Those airlines are also responsible for some of the main changes in the airports operations and market positioning. The increase in routes and frequencies offered by these airlines enabled the emergence of new tourist destinations in Europe that spread, later on, to other places all over the world. The ease of purchasing an airline ticket online, and the availability of attractive routes at affordable prices allowed the development of new market segments, such as second home tourism. One of the main impacts of low cost operations has been the changing of airport's structures, mainly to the ones that traditionally received charter flights. In this article we are going to explore the case study of Faro airport, an excellent example of these changes.